Analisis Dampak Utang terhadap Perekonomian Indonesia Periode 1976-2021: - Salistia, Faisal; Arsyad, Muhammad Rizal; Junaedi, Dedi; Paramansyah, Arman; Norman, Efrita; Hermaliana, Mia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Foreign debt has an important and inseparable role in the history of Indonesia's national development. The government has changed seven times, foreign debt is always present to fill the development budget deficit. Debt is expected to help move the wheels of the economy, create growth, create jobs, and alleviate poverty. This study aims to analyze the effect of debt, budget, inflation and differences in government regimes on the Indonesian economy (GDP and Income per Capita) in Indonesia for the 1976-2021 period. The study uses secondary data obtained from Bank Indonesia, the National Development Planning Agency (Bappenas), the Central Statistics Agency (BPS), the World Bank, and other reference sources such as books, journals and scientific papers. The data used are the value of foreign debt, APBN, national income (GDP), population, inflation rate, and government regime in the period 1976 - 2021. The results of multiple regression analysis with dummy variables (using the Eviews 10 application program) show the following results: Foreign debt and APBN have a correlation with the condition of the national economy, especially the value of GDP. Debt and the state budget tend to increase the value of GDP. In terms of debt management as a driver of economic growth, the Suharto Era (New Order) tended to be better than the eras that followed. However, relatively speaking, the Habibe and SBY eras tended to be better than the Megawati era, the Abdurahman Wahid era, and the Jokowi era. In fact, Jokowi's era is no better than previous eras. Keywords: Budget, Inflation, GDP, Indonesian Economy